Leptin and inflammatory pathways in the Alzheimer's disease continuum: Implications for glial activation and neuropsychiatric symptoms - Fumihiko Yasuno; Kazuyuki Nakagome; Yoshie Omachi; Yasuyuki Kimura; Aya Ogata; Hiroshi Ikenuma; Junichiro Abe; Hiroyuki Minami; Takashi Nihashi; Kastunori Yokoi; Saori Hattori; Nobuyoshi Shimoda; et al. (Brain, Behavior, & Immunity - Health)
Introduction: Chronic peripheral inflammation triggered by adipokine release may extend to the brain, potentially influencing the pathological progression of Alzheimer's disease (AD) and neuropsychiatric symptoms (NPS). However, it remains unclear whether and how leptin contributes to the link between adipose tissue dysfunction and dementia. This study aims to investigate the role of leptin in the connection between adipose-derived inflammatory signaling and cognitive impairment/NPS. Methods: Path analysis was employed to explore how leptin relates to the association between adipose-related metabolic dysfunction and dementia through inflammatory pathways in patients with AD pathology (n = 15). Variables included plasma leptin concentration, body mass index (BMI) as a marker of adiposity, and in vivo assessments of regional neuroinflammation using translocator protein (TSPO)-PET imaging with the tracer 11C-DPA-713 (11C-DPA-713-binding potential [11C-DPA-713-BPND]). Cognitive function was measured using the Alzheimer's Disease Assessment Scale-Japanese Cognitive Subscale (ADAS-J cog), while NPS were assessed using the Neuropsychiatric Inventory Questionnaire (NPI-Q). Results: Regression analysis demonstrated that higher plasma leptin concentrations positively correlated with BMI and significantly predicted 11C-DPA-713-BPND in the insula. Additionally, NPI-Q scores were associated with 11C-DPA-713-BPND in the insula. Path analysis supported leptin's role linking adiposity to NPS through insular inflammation. The hypothesized model fit the data well under the null hypothesis [χ2 (3) = 0.63, p = 0.89]. Discussion: These findings underscore the relevance of exploring how leptin and adipose tissue dysfunction interact with neuroinflammatory processes in contributing to NPS in the patients in the AD continuum. Interventions targeting these interactions could represent promising avenues for managing NPS.